Emotion, empathic and moral processing in personality disordered offenders - Marsden, Janet (2021)
This thesis provides a diverse and detailed account of research that has examined emotion, empathic and moral processing in antisocial personality disordered (ASPD) and dissocial personality disordered (DPD) populations with and without co-morbid psychopathy. It incorporates a systematic review, empirical research and a psychometric critique and in doing so provides a comprehensive overview of the methods employed to examine these constructs and findings which inform how emotion, empathic and moral processing manifest in these groups.